Synthesis of 2-substituted 9-oxa-guanines {5-aminooxazolo[5,4-d]pyrimidin-7(6H)-ones} and 9-oxa-2-thio-xanthines {5-mercaptooxazolo[5,4-d]pyrimidin-7(6H)-ones} - Mandal, Subrata; Li, Wen Tai; Bai, Yan; Robertus, Jon D.; Kerwin, Sean M. (Beilstein Journal of Organic Chemistry, 2008)
Oxazolo[5,4-d]pyrimidines can be considered as 9-oxa-purine analogs of naturally occurring nucleic acid bases. Interest in this ring system has increased due to recent reports of biologically active derivatives. In particular, 5-aminooxazolo[5,4-d]pyrimidine-7(6H)-ones (9-oxa-guanines) have been shown to inhibit ricin. The preparation of a series of 2-substituted 5-aminooxazolo[5,4-d]pyrimidin-7(6H)-ones and related 5-thio-oxazolo[5,4-d]pyrimidines is described, including analogs suitable for further elaboration employing “click” chemistry utilizing copper-catalyzed Huisgen 1,3-dipolar cycloadditions. Two of the compounds prepared were found to inhibit ricin with IC50 ca. 1–3 mM.
Keywords: Annulation; Click Chemistry; Cyclization; Purine Analogs; Ricin